Context Matters in the Effectiveness of Emotion Regulation Strategies - Anna-Lena Rottweiler; Jamie L. Taxer; Ulrike E. Nett (SAGE Publishing, 2018)
In the time before an upcoming exam, anxiety is an omnipresent emotion that students may choose to regulate. To date, emotion regulation strategies have been examined in everyday life, but little is known about how these strategies work in exam-related contexts. Therefore, our aim was to explore the effectiveness of several emotion regulation strategies across two contexts (exam-related vs. non-exam-related anxiety). A total of 68 university students participated in an experience sampling study for 6 days prior to an important exam. Suppression improved mood in exam-related anxiety, while distraction improved mood only in non-exam-related anxiety. Considering these differing effects, it is important to not unilaterally classify emotion regulation strategies into effective versus ineffective but to also consider the context in which the emotion is experienced.